COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND AFTER THE IMPLEMENTATION OF BRANCHLESS BANKING IN CONVENTIONAL COMMERCIAL BANKS - frisca widya lestari; Nizwan Zukhri; Darman Saputra (Ekspektra : Jurnal Bisnis dan Manajemen, 2023)
This study aims to analyze the comparison of the financial performance of conventional commercial banks before and after the implementation of branchless banks, namely by measuring the ratios of Return on Assets (ROA), Operational Costs and Operating Income (BOPO), Loan to Deposit Ratio (LDR) and Capital Adequacy Ratio (CAR). This research is a comparative study with a total sample of 7 conventional commercial banks, the sampling of which uses a purposive sampling technique so that the object of research is conventional commercial banks that have not implemented Branchless Banking for five years (2010-2014) and five years after the implementation of Branchless Banking (2015- 2019). Testing the instrument using descriptive analysis and normality test, while for the analytical method using the Paired sample t-test for normally distributed data and the Wilcoxon signed rank test for abnormally distributed data through the SPSS 25 program. The results of this study indicate that based on the results of the Paired test sample t-test on the ROA, BOPO and CAR variables obtained a significance value of 0.00 <0.05, then the RAO, BOPO and CAR variables have significant differences after the implementation of Branchless Banking. Furthermore, based on the Wilcoxon signed rank test on the LDR variable, a significance value of 0.00 <0.05 was obtained, so the LDR variable had a significant difference after the implementation of Branchless Banking. Keywords: Branchless Banking, ROA, BOPO, LDR, CAR